Roll‐to‐Roll Sputter Coating of Aluminum Cathodes for Large‐Scale Fabrication of Organic Photovoltaic Devices. Issue 4 (12th February 2015) - Griffith, Matthew J.; Cooling, Nathan A.; Vaughan, Ben; O'Donnell, Kane M.; Al‐Mudhaffer, Mohammed F.; Al‐Ahmad, Alaa; Noori, Mahir; Almyahi, Furqan; Belcher, Warwick J.; Dastoor, Paul C.
Abstract: We report the demonstration of sputter‐coated aluminum contacts directly onto P3HT:PCBM organic photovoltaic devices using a R2R process without detrimentally influencing the performance of the devices. The final sputtered devices do not require any protective buffer layers to produce efficient performance. Depth profiling analysis of sputtered films using X‐ray photoelectron spectroscopy (XPS) indicated the presence of a 5–6 nm insulating oxide layer generated at the cathode interface for all sputtering target power densities greater than 1.4 W cm −2 . The aluminum penetration into the P3HT:PCBM film was found to be consistent with the depth of this oxide layer, suggesting that aluminum penetration into the organic film is not the primary reason for performance limitations in sputtered devices. Introduction of thermally evaporated aluminum buffer layers prior to deposition of sputtered aluminum cathodes demonstrated that the performance of devices after annealing matched those of reference devices prepared with no sputtering for a buffer layer thickness of only 20 nm. Further analysis of the device J ‐ ‐V curves revealed an S‐shaped kink prior to annealing, indicating that the major reason for the poor performance in sputtered devices was the introduction of a charge extraction barrier at the cathode, which was subsequently removed upon annealing. Rigorous removal of oxygen from the sputtering chamber prior to aluminum deposition onto the P3HT:PCBM active layer was subsequently observed to produce a device with an efficiency close to that of the thermally evaporated reference device without the requirement for evaporated buffer layers. The results presented here highlight a pathway towards an alternative R2R cathode fabrication technique that allows the highly efficient aluminum cathodes employed in small‐scale devices to be transferred onto large‐scale, flexible, and low‐cost R2R printed organic electronic devices. Abstract : The fine print : Here we demonstrate the viability of R2R sputter coating to prepare aluminum cathodes for printable OPV devices without damaging the organic films. We show that oxidation of deposited metal films is the key mechanism that has restricted performance. By modifying the vacuum processing procedure to remove residual oxygen contaminants during sputtering, we produce OPV devices with a performance close to that of reference samples with an evaporated cathode.